Development of Differentiated Learning-Based Interactive Media to Overcome Difficulties in Learning Science in Grade IV/Islamic Elementary School Students - Heryani; Trinova, Zulvia; Frasandy, Rendy Nugraha; Sutarsih, Cicih (International Conference on Elementary Education, 2025)
This research aims to develop interactive media based on differentiated learning to overcome the learning difficulties of IPAS students in grade IV of SD/MI. This research is a Research and Development (R&D) research, using a 4D development model consisting of the stages of definition, design, development and dissemination. The subjects of this study are 71 students and 3 educators who will conduct a media practicality test, media experts, linguists, and material experts. Data collection techniques were carried out by observation, interviews and questionnaires. The results of the study show that interactive media is valid and practical in overcoming learning difficulties in learning IPAS. Interactive media was declared valid in terms of language with a percentage of 94%, material with a percentage of 90% and media with a percentage of 96% so that an average of 93.3% was obtained with a very valid category. The practicality of interactive media by educators and students was obtained on average 94% by educators in the Very Practical category and 89.4% by students in the Very Practical category. The development of differentiated learning-based interactive media products does not use an effectiveness test but only uses a validity test and a practicality test. Based on these results, it can be concluded that differentiated learning-based interactive media to overcome learning difficulties in learning science in grade IV of SD/MI is categorized as very valid and very practical and can overcome students' learning difficulties in learning science.